Thinking vs. Thought in the context of David Bohm: The Awakening of Creativity as Opposed to Arbitrariness and Fragmentation of Scientific Knowledge - André, Juliana Genevieve Souza (2021)
This present Doctoral Thesis deals with David Bohm's reflection on the Act of Thinking vs. Thinking, and its impacts that would affect freedom for creativity, or, on the contrary, would run into arbitrariness and fragmentation, especially in scientific knowledge. For that, we combined some of his works, written in the period of his maturity. In the weaving of our text, following the line of Bohm, we resort to the use of metaphors and analogies, in order to explore not only the “awakening of his creativity”, through the contexts to which he was involved, but also his repertoire, their lenses to understand the world involved and explained. In addition, we analyze how their affective bonds would have contributed to their particular way of making themselves: as a physicist and free thinker. Although he was a scholar born in the last century, we will see how other researchers, even today, seem to share the "same" act of thinking, which in a way, even if implied, continues to extend its influence to many.